An agricultural atlas of Nigeria - Agboola, S. A. (Oxford : New York : Oxford University Press, 1979)
This book is mainly concerned with space utilization in Nigerian agriculture and the problems of increased production..
Includes index.
Includes bibliographical references: p. 211-230
ijb 18/12/2018
Ref.
Keywords: Agriculture; Agriculture--Economic aspects; Nigeria